Os sentidos sociais da velhice e do envelhecimento nos programas de preparação para aposentadoria de grandes empresas brasileiras - Bernardinelli, Ingrid (2020)
In recent years, the number of large companies that have implemented retirement preparation programs has increased, which stems from their perception of demographic changes and the need for intervention in their employees' retirement processes. The objective of the research is to analyze the social conceptions of old age and aging underlying the retirement preparation programs of Brazilian companies. To achieve the proposed objective, a qualitative research, focused on analyzing, investigating and incorporating the meanings and interpretations attributed to the programs and the individuals involved, was carried out. Using secondary data about management literature and reports published in the business media, and primary data, collected through semi-structured interviews with consultants that rely on these programs and Brazilian companies. These data were analyzed based on the technique of content analysis. The concept of old age underlying the programs has been shown to be positive, since it agrees with a more active retirement. This transformation is in line with analyzes that point to recent ideological transformations that value the idea of activity and the financialization process. Corporate retirement preparation programs encourage an investment culture, of which the topic of financial planning is highlighted. Such programs spread as an opportunity to engage in new activities after retirement, such as economic activities and entrepreneurial activities, and with that, builds new perspectives for retirement. The understanding of the meanings underlying these programs is relevant, since large companies and consultancies are influential actors in the construction of meanings about old age and aging, influencing the ways in which society in general understands the phenomenon and influencing the ways that many people plan for retirement, deconstructing old-fashioned views of old age and rebuilding it as a new, more active phase.